Group classification of systems of nonlinear reaction-diffusion equations with triangular diffusion matrix - Nikitin, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We complete the group classification of systems of two coupled nonlinear reaction-diffusion equations with general diffusion matrix begun in author’s previous works. Namely, all nonequivalent equations with triangular diffusion matrix are classified. In addition, we describe symmetries of diffusion systems with nilpotent diffusion matrix and additional terms with first-order derivatives.